Assessment and Evaluation of Emergency Remote Teaching for a Project-Based Assignment on the Production of Eco-Innovative Food Products – A Case Study - Maria Katsouli; Virginia Giannou; Petros Taoukis (International Journal of Food Studies)
Institutions of Higher Education (HEIs) faced great challenges, due to the COVID- crisis, on swiftly dealing with this unprecedented situation regarding the implementation of practical courses and interactive educational activities such as project-based courses. The aim of this work is to analyze the challenges and difficulties that arose through this process and the benefits that have emerged for both students and educators. For this reason, questionnaires were designed to study the pedagogical practices used for a project-based course, during the pandemic, and were distributed online to all students and supervisors enrolled in the course. The course entailed the design of an innovative food product, from the interactive analysis of different novel ideas to the production of a final product of high nutritional and ecological profile. Despite the concern that the enforcement of distance learning would significantly affect project-based courses, the majority of respondents confirmed that their institution adapted the curriculum successfully. They also declared satisfaction with the general format, and teaching procedures adopted, and agreed that the online modality can properly transmit educational content. Although, both faculty and students needed to adapt to the distance learning modality and become familiar with the use of new digital tools, they agreed that it can be very useful and provide benefits, when properly planned in advance and accompanied by the right technical support, equipment and class materials.